PENGEMBANGAN E-MODUL BERBASIS METODE INKUIRI PADA PEMBELAJARAN TEMA 6 SUBTEMA 3 UNTUK KELAS V SDN 21 PEKANBARU - Susti Nanda Giatri; Dea Mustika (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2022)
This article describes the inquiry method based on e-modules development and determines the validity of inquiry-based e-module development. The research described in this article is research and development with the ADDIE model, which was limited to the development stage. The validators of the research were tested by two material experts, two design experts, and two linguists. The data collection method used interviews, questionnaire validation sheets, and documentation. The result was e-module development based on the inquiry method process that began with the needs analysis stage, the curriculum, and the learning materials. Subsequently, the product design stage was conducted so that it could be continued at the validity stage. The development of e-modules on thematic learning in sub-theme 6 of theme 3 for grade V students of SDN 21 Pekanbaru could be applied as teaching and learning materials or student teaching handbooks. And it has found the criteria very well with an average validity percentage score of 95%. The module that was tested by design experts at 97%, material experts at 92%, and linguists with a percentage score of 97% were very valid to use. The researcher suggested that it is necessary to apply e-modules in order to determine the effectiveness and practicality in applying it during the teaching and learning process in the classroom.